Promoting Total Physical Response for Teaching English Vocabulary in Secondary School across Pekalongan Regency: Teachers' Perspective on its Application - Ghani, Irfan; Setyaji, Arso; Hawa, Faiza (Jetlal, 2025)
Teaching English vocabulary is very important because vocabulary has an important role in communication. The Total Physical Response (TPR) method is considered an effective method in teaching vocabulary. This research focuses on teachers' perspectives on teaching English vocabulary using the Total Physical Response (TPR) method. Data was collected using a survey in the form of a closed-ended questionnaire focusing in the area of teachers' perspective, usefulness, advantages, disadvantages and obstacles. The survey was sent to English Teachers Association in Pekalongan Regency. Thirty (30) English teachers participated in this research. The results show that the Total Physical Response (TPR) method helps teachers in teaching vocabulary. However, teachers also encounter obstacles when teaching vocabulary using the TPR method. This research serves the use of Total Physical Response (TPR) method in teaching vocabulary which emphasizes the teacher's perspective on its application.